Fire hazard zonation of Bardia National Park, Nepal: A disaster preparedness approach - Ghimire, B.; Bhujel, K.; Rijal, K. (Nepal Journal of Environmental Science, 2014)
This study was focused to prepare fire hazard map of Bardia National Park (BNP) through fire hazard zonation model. BNP is located at western Terai (lowland plains) of Nepal. The model was prepared by using four sub-models. The sub-models were prepared by considering nine parameters selected on the basis of their significance in fire risk assessments and their data availability. Remotely sensed data and Geographic Information System (GIS) were used during model preparation and validation process. The output map from the model was validated using Moderate Resolution Imaging Spectroradiometer (MODIS) active fire points (2001- May 2014) within BNP. Very high fire risk areas were identified along southern boundary; Northeast and Northwest part of the park covering about 5% of the park area. Similarly, about 31% of the park area was identified as high risk zone and 31.43% area of BNP was identified as medium risk zone. MODIS active fire data was very useful for validation process that showed proportionate result with the area coverage of predicted risk classes. The validation result suggests that this prepared model can be used to prepare fire hazard zonation maps and preparedness plans of areas similar to BNP. The plans to prevent and control wildfire in BNP should be focused on high risk areas through preparedness initiatives, awareness activities and capacity building of fire fighting team. Reducing surface fuel load and fuel continuity during pre-fire season (Dec-Feb) in general and particularly during February shall reduce fire occurrences and its damage to a great extent.